The Flower of San Remo. Il Gattopardo on Location - Nicholls, Mark (Spunti e Ricerche, 2021)
Considering the production of Il Gattopardo in Sicily, and some pre-production business, this article seeks to account for the substance of this particular encounter and to expand our understanding of the issues that are raised when a visiting, foreign film company comes to town and endeavours to tell a story which purports to be about local histories and cultures. These issues are explored by way of a creative practice analysis which stands as a useful method in understanding the somewhat neglected and frequently mythologised pursuit of social history within the creative arts. The article focuses on the most detailed and comprehensive accounts of the production provided in the work of Tommaso Cima (1963), Alberto Anile and M. Gabriella Giannice (2013) and in the documentary film A Dying Breed: The Making of The Leopard, produced as part of the Criterion Collection DVD release of 2004. From these accounts and the primary evidence that they provide, it offers an overview of the production of the film in Sicily and assesses the extent to which it engaged with local places and people. In doing so, it reflects on what this encounter tells us about how significant Sicily itself was to Il Gattopardo. The article offers an analysis of these events and encounters and considers what the standard business of location filming, such as location scouting, negotiating with individuals and institutions, building and renovation works, on-set improvisation and adaptation to local conditions and cultures, tells us about this production’s commitment to Sicily.